2022
DOI: 10.1021/acs.cgd.2c00900
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Two Three-Dimensional Co(II)-Based Metal–Organic Frameworks as Quercetin Anticancer Drug Carriers

Abstract: Two three-dimentional Co-based metal–organic frameworks with the formulae of [Co3(2-BrTPA)3].(DMF)4 (MUT-6) and [Co5(DBrTPA)4(DMF)6(HCOO)2] (MUT-7) [2-BrTPA = 2-bromoterephthalic acid, DBrTPA = 2,5-dibromoterephthalic acid] were synthesized through various synthetic techniques. The structures were fully characterized using a series of techniques, and the crystal structures were solved using single-crystal X-ray crystallography. Furthermore, the solvent stability test was conducted in various organic solvents. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 116 publications
0
10
0
Order By: Relevance
“…IR (KBr pellet, cm –1 ): 3445 (w), 1631 (s), 1585 (s), 1390 (w), 1346 (s), 1153 (s), 1106 (s), 908 (s), 829 (s), 771 (w), 676 (s), 539 (s). For CoMOF-2, according to a previous report, Co­(NO 3 ) 2 ·6H 2 O (0.291 g, 1 mmol) and H 2 DBrTPA (0.161 g, 0.5 mmol) were put into 20 mL of DMF and then ultrasonically treated for 30 min to mix evenly. Then, the suspension was transerred into a 25 mL Teflon-lined steel autoclave and heated at 120 °C for 72 h; the red block crystals of CoMOF-2 were obtained with a 63% yield after cooling to room temperature at 10 °C/h.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…IR (KBr pellet, cm –1 ): 3445 (w), 1631 (s), 1585 (s), 1390 (w), 1346 (s), 1153 (s), 1106 (s), 908 (s), 829 (s), 771 (w), 676 (s), 539 (s). For CoMOF-2, according to a previous report, Co­(NO 3 ) 2 ·6H 2 O (0.291 g, 1 mmol) and H 2 DBrTPA (0.161 g, 0.5 mmol) were put into 20 mL of DMF and then ultrasonically treated for 30 min to mix evenly. Then, the suspension was transerred into a 25 mL Teflon-lined steel autoclave and heated at 120 °C for 72 h; the red block crystals of CoMOF-2 were obtained with a 63% yield after cooling to room temperature at 10 °C/h.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…Thus, the development of materials with optimal CO 2 binding energies and high selectivity is a complex issue with considerable practical implications. MOFs are porous inorganic materials that have received much attention recently owing to their outstanding characteristics, such as significant surface area and porosity, thermal/chemical stability, and tunability. MOFs are considered promising materials for a variety of potential applications across various fields, including gas storage and separation, chemical sensing, biomedical applications, adsorption, and heterogeneous catalysis. They are considered as one of the most promising physical adsorbent materials in the process of separating CO 2 /CH 4 . The engineering design of MOFs for gas separation applications is currently a rapidly growing area of research. Numerous experimental and simulation-based studies have been documented involving the separation of CO 2 from CH 4 through the use of MOFs. Considering the quadrupole moment and polarizability of CO 2 , current research efforts to enhance CO 2 uptake and selectivity primarily involves strategies aimed at improving the interaction between CO 2 and the frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…GCMC simulation was employed to gain valuable insights into the adsorption behavior of 5-fluorouracil on various MOFs including IRMOF-1, IRMOF-8, IRMOF-10, Mg-MOF74, Fe-MOF74, Cu-MOF74, and Zn-MOF74 . Recent computational studies by our research group have identified MOF-123, MUT-3, and MUT-2 as potential carriers of 5-FU. , Moreover, our research group has evaluated MUT-6 and MUT-7 as candidates for carrying Quercetin …”
Section: Introductionmentioning
confidence: 99%
“…62,63 Moreover, our research group has evaluated MUT-6 and MUT-7 as candidates for carrying Quercetin. 64 In this research, a new Mg-based MOF was synthesized and characterized [Mg 5 (DBrTPA) 4 (DMF) 6 (HCOO) 2 ] (MUT-8) [DBrTPA = 2,5-dibromoterephthalic acid, MUT = Materials from the University of Tehran] through a solvothermal reaction with and without ultrasonic radiation. Some characterizations such as FT-IR, PXRD, TGA, and FE-SEM analyses were conducted to evaluate the structure of MUT-8.…”
Section: Introductionmentioning
confidence: 99%